Sensitivity study of APR-1400 steam generator primary head stay cylinder and tube sheet thickness. (June 2016) - Abdallah, Khaled Atya Ahmed; Namgung, Ihn
Highlights: Tubesheet thickness reduction. Increasing stiffness of tubesheet. Optimal design of tubesheet. Abstract: The steam generator is a type of heat exchanger which produces steam to drive the turbine generator. For the APR-1400, Doosan Heavy Industries & Construction manufactures a vertical type of steam generator that has a horizontal tube sheet with a central support design, called a stay cylinder. In this design, the stay cylinder limits tube sheet deformation and effectively reduces thickness of tube sheet and increases structural integrity. A concentric hole in the stay cylinder facilitates welding to the primary head and to the tube sheet. In this study, the APR-1400 steam generator tube sheet thickness parameters were investigated within the constraint of maintaining the overall deformation of the tube sheet in comparison to the current design. A parametric evaluation to reduce the thickness of the steam generator tube sheet is performed by varying the inner diameter of the stay cylinder and the thickness of the tube sheet. The solutions are developed based on two-dimensional finite element analyses. The effect of a reduction of the tube sheet is beneficial in the manufacturing of steam generator by using less material and reducing manufacturing time and allowing easier assembly process of U-tube bundles to the tube sheet.